Mythology of Parkinson’s disease: from levodopa phobia to dopamine agonist phobia - O. S. Levin (Медицинский совет, 2020)
Any common disease (including Parkinson’s disease) is inevitably overgrown with myths. As a result, not scientifically grounded approaches based on the principles of evidence-based medicine, but irrational ideas, especially often of a pharmacophobic nature, begin to dominate in primary clinical practice among doctors and patients. In clinical practice, we can often face to a situation when doctors, dogmatically accepting the principle of delayed initiation of levodopa therapy, for a long time try to guide the patient on other antiparkinsonian drugs, despite the obvious ineffectiveness of such therapy and the increasingly growing immobility of the patient. This phenomenon, based on the irrational beliefs of not only doctors, but also patients in the toxicity of levodopa, is commonly referred to as levodopa phobia. Levodopa phobia, along with the emergence of a new generation of dopamine agonists (DAs), whose ability to delay the development of fluctuations and dyskinesias has been proven in a series of placebo-controlled studies, as well as the erroneous interpretation of the withdrawal syndrome of DAs as evidence of their high effectiveness, have led to the widespread use of this class. drugs. However, the use of DA turned out to be associated with an increased risk of such adverse events as daytime sleepiness, leg edema, impulsive-compulsive disorders, and withdrawal syndrome. All this served as the basis for the appearance of “dopamine agonists phobia”, which can lead to unjustifiably early prescription of levodopa and the development of dyskinesias. What is the optimal way for managementof PD patients today? In our opinion, the patient management formula that doctors should adhere to should be as follows: early prescription of dopaminergic drugs (more often DAs or levodopa) is necessary, which provides a quick possible, albeit incomplete, correction of a motor defect, which would be sufficient to preserve the patient’s motor activity, including his professional activity; as the symptoms increase, an escalation of antiparkinsonian therapy with the sequential addition of levodopa (or DAs), MAO B inhibitors, amantadines is necessary.